2003
DOI: 10.1557/jmr.2003.0259
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rare-earth oxide and alumina additives on thermal conductivity of liquid-phase-sintered silicon carbide

Abstract: by hot pressing and annealing. Their microstructures, phase compositions, lattice oxygen contents, and thermal conductivities were evaluated. The SiC doped with rare-earth oxides attained thermal conductivities in excess of 200 W/(m K); however, the SiC doped with additives containing alumina had thermal conductivities lower than 71 W/(m K). The high thermal conductivity of the rare-earth-oxide-doped SiC was attributed to the low oxygen content in SiC lattice, high SiC-SiC contiguity, and lack of ␤to ␣-SiC pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
2
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 36 publications
1
51
2
1
Order By: Relevance
“…Thermal diffusivity was measured by the laser‐flash method (Model TC‐7000, ULVAC, Yokohama, Japan). The details of thermal diffusivity measurement can be found elsewhere 32 . Before measurement, the surfaces of the specimens were sputter coated a 600 Å thick layer of gold to avoid direct transmission of the laser pulse, followed by a subsequent coating of colloidal graphite to enhance absorption of the flash energy.…”
Section: Methodsmentioning
confidence: 99%
“…Thermal diffusivity was measured by the laser‐flash method (Model TC‐7000, ULVAC, Yokohama, Japan). The details of thermal diffusivity measurement can be found elsewhere 32 . Before measurement, the surfaces of the specimens were sputter coated a 600 Å thick layer of gold to avoid direct transmission of the laser pulse, followed by a subsequent coating of colloidal graphite to enhance absorption of the flash energy.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that by tailoring the glassy phase composition in liquid-phase sintered silicon carbide, the thermal conductivity can be doubled. 19 Furthermore, a reduction on the glassy phase content increases the thermal conductivity of a composite, k c .…”
Section: Introductionmentioning
confidence: 99%
“…P ressureless , liquid‐phase‐sintered (LPS) silicon carbide (SiC) ceramics with oxide additives (Al 2 O 3 , Y 2 O 3 ) possess remarkable mechanical and thermal properties, which, combined with the ease and economy of pressureless processing, makes LPS SiC attractive structural materials 1–12 . The majority of studies on the mechanical properties of LPS SiC have been limited to strength, toughness, hardness, contact behavior, and high‐temperature behavior.…”
Section: Introductionmentioning
confidence: 99%